2016
DOI: 10.1371/journal.pone.0152473
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling Regulates Sleep Stability

Abstract: The hypnogenic properties of cannabis have been recognized for centuries, but endogenous cannabinoid (endocannabinoid) regulation of vigilance states is poorly characterized. We report findings from a series of experiments in mice measuring sleep with polysomnography after various systemic pharmacological manipulations of the endocannabinoid system. Rapid, unbiased scoring of vigilance states was achieved using an automated algorithm that we devised and validated. Increasing endocannabinoid tone with a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 82 publications
5
64
1
Order By: Relevance
“…However, evidence showing an apparent opposite modulatory role of the CB 1 cannabinoid receptor in sleep modulation has been published as well. In this regard, injection of the antagonist/inverse agonist AM281 of the CB 1 cannabinoid receptor immediately after TSD did not obstructed sleep rebound (Pava et al, 2016). Moreover, SWS was increased during the dark period after administrations of higher dose of CP47497, a cannabinoid receptor agonist, while reduction in this sleep stage was observed across the light period (Pava et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, evidence showing an apparent opposite modulatory role of the CB 1 cannabinoid receptor in sleep modulation has been published as well. In this regard, injection of the antagonist/inverse agonist AM281 of the CB 1 cannabinoid receptor immediately after TSD did not obstructed sleep rebound (Pava et al, 2016). Moreover, SWS was increased during the dark period after administrations of higher dose of CP47497, a cannabinoid receptor agonist, while reduction in this sleep stage was observed across the light period (Pava et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, injection of the antagonist/inverse agonist AM281 of the CB 1 cannabinoid receptor immediately after TSD did not obstructed sleep rebound (Pava et al, 2016). Moreover, SWS was increased during the dark period after administrations of higher dose of CP47497, a cannabinoid receptor agonist, while reduction in this sleep stage was observed across the light period (Pava et al, 2016). The intriguing but as yet unexplained results that CB 1 cannabinoid receptor modulates sleep raises questions about the mechanism of action implied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, cumulative evidence has suggested that the elements of the endocannabinoid system, including FAAH, control the sleep-wake cycle (Santucci et al, 1996; Murillo-RodrĂ­guez et al, 1998, 2001, 2003, 2008a, 2011a, 2013, 2016; Herrera-Solis et al, 2010; Rueda-Orozco et al, 2010; Pava et al, 2014, 2016). In this regard, an experimental approach to explore the role of FAAH in sleep modulation has consisted in the characterization of the properties of FAAH inhibitors, such as URB597 (Murillo-RodrĂ­guez et al, 2007b, 2011a, 2016).…”
Section: Discussionmentioning
confidence: 99%